IMPLEMENTASI PEMBAGIAN TUGAS PADA TOP MANAGEMENT PT ISS INDONESIA - Alisa Qotrunnada; Dira Ayudirahma; Lavia Prakasiwa; Khotijah Khotijah; Reni Widyastuti (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study aims to analyze the implementation of task allocation within the top management of PT ISS Indonesia and the role of the Management Information System (MIS) in supporting the effectiveness of this managerial structure. PT ISS Indonesia, as a national-scale facility services provider, faces high operational complexity, requiring a clear, focused, and coordinated task allocation at the top management level. This study employed a literature review method, reviewing books, scientific journals, and related documents relevant to top management, management information systems, and organizational effectiveness. The results indicate that a structured task allocation between the directors of operations, commercial affairs, finance, people & culture, legal & compliance, and the strategic and HSEQ directorates can improve decision-making effectiveness, coordination, and operational efficiency. Furthermore, the MIS plays a crucial role in providing real- time data, streamlining communication, supporting resource allocation, and simplifying monitoring and evaluation processes. Overall, the implementation of a clear task allocation and MIS support has been proven to strengthen top management performance and support the quality of PT ISS Indonesia's services.